ANALISIS MINAT BELAJAR SISWA MATA PELAJARAN IPS KELAS VII C SMP NEGERI 11 PONTIANAK - Riska Wahyuni; Junaidi H Matsum; Sulistyarini Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to explain and analyze studen’s interest in social science subject of SMP Negeri 11 Pontianak in VII C. the purpose of this study is to learn about student’s interest in learning is reflected in the student’s likes, attention, interest and involvement in social science subject. This research uses a qualitative approach with a descriptive method. The data collection teqhniques used are observation techniques, interview and documentation studies while the data collection tools are observation guides, interview guides, documentation. Studies show that (1) student’s liking for social science subject in class VIIC is said to be good. (2) student’s attention to social science subject in class VIIC is said to be good enough. (3) student’s interest in social science subject in class VIIC is said to be good enough. (4) student’s involvement in social science subject in class VIIC is said to be good.  . Keywords: analysis, learning interest, social studies.